2021
DOI: 10.5194/acp-2021-298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on the seasonal variation of Aeolus detection performance over China using ERA5 and radiosonde data

Abstract: Abstract. Aeolus wind products have been available to ordinary users on May 12, 2020. In this paper, the Aeolus wind observations, L-band radiosonde (L-band RS) data and the European Centre for Medium-Range Weather Forecasts (ECMWF) fifth generation atmospheric reanalyses (ERA5) are used to analyse the seasonality of Aeolus detection performance over China. Based on the Rayleigh-clear data and Mie-cloudy data, the data quality of the Aeolus effective detection data is verified, and the results show that the Ae… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This product consists of 10 sources with a time resolution of 3 hours (Hersbach et al 2020). Chen et al (2021) showed that ERA5 data on wind speed are reliable in most areas of Guangdong and the area near the coast of Guangdong. Yang et al (2019) found that the accuracy of precipitable water data provided by ERA5 is better than that of ERA-interim, and both reanalysis data fully re ect the annual variability of precipitable water, but the daily variability deviation of ERA5 is generally smaller than that of ERA-interim.…”
Section: Methodsmentioning
confidence: 99%
“…This product consists of 10 sources with a time resolution of 3 hours (Hersbach et al 2020). Chen et al (2021) showed that ERA5 data on wind speed are reliable in most areas of Guangdong and the area near the coast of Guangdong. Yang et al (2019) found that the accuracy of precipitable water data provided by ERA5 is better than that of ERA-interim, and both reanalysis data fully re ect the annual variability of precipitable water, but the daily variability deviation of ERA5 is generally smaller than that of ERA-interim.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the switch-over from the first flight model laser (FM-A) to the redundant laser FM-B just after AVATARE in June 2019 marked a caesura, as the FM-B delivered much higher emit energy and hence ensured higher signal-to-noise ratio of the backscatter return compared to the end of the FM-A period (Lux et al 2020b;Lux et al, 2021). Moreover, the satellite instrument was found to be more susceptible to changes in the thermal environment than expected before launch showing orbital and seasonal variations in the beam alignment, and hence in the wind bias (Martin et al, 2021;Chen et al, 2021). This issue, together with the influence of the seasonally varying solar background being incident on the instrument spectrometers and affecting the wind measurement precision, could be investigated based on the comparative wind measurements from the AVATARE and AVATARI campaigns.…”
Section: Overview Of Validation Campaigns and Datasetsmentioning
confidence: 99%
“…The availability of the Aeolus dataset provides the unique opportunity to directly assess the performance of AMVs derived from different retrieval channels relative to a global reference wind profile dataset observed by a single unit. Such a direct comparison has not previously been possible due to the sparse spatial coverage of other available reference datasets, e.g., rawinsonde winds (e.g., Chen et al, 2021;Liu, B. et al, 2021;Martin et al, 2021). Further, Aeolus observations are made at a set of fixed vertical levels that represent the averages of accumulated measurements within vertical range bins.…”
Section: Introductionmentioning
confidence: 99%